2011
DOI: 10.1093/jscr/2011.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplastic sublingual gland in association with a congenitally missing ipsilateral submandibular gland

Abstract: A congenitally absent unilateral submandibular gland is a rare condition. We present such a case with an associated ipsilateral benign hyperplastic sublingual gland. The enlarged sublingual gland may well represent a compensatory response to the missing submandibular gland, but it is known that sublingual gland tumours are malignant in approximately 90% of cases and so a sublingual gland swelling is viewed with a high degree of suspicion. Clinical diagnosis of sublingual hyperplasia becomes a challenge if ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Lee et al reported a case of unilateral SMG aplasia with thyroglossal duct cyst that might have developed as an ectopic SMG with ipsilateral unilateral SMG aplasia. Gangidi and Cunliffe reported a case of a hyperplastic sublingual gland with the absence of ipsilateral SMG. Fine‐needle aspiration was performed and the cytology report confirmed the presence of salivary gland cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al reported a case of unilateral SMG aplasia with thyroglossal duct cyst that might have developed as an ectopic SMG with ipsilateral unilateral SMG aplasia. Gangidi and Cunliffe reported a case of a hyperplastic sublingual gland with the absence of ipsilateral SMG. Fine‐needle aspiration was performed and the cytology report confirmed the presence of salivary gland cells.…”
Section: Discussionmentioning
confidence: 99%
“…The congenital absence of multiple major salivary glands may be associated with ectodermic defects of the first and second branchial arches, agenesis of the lacrimal glands and lacrimal punctum aplasia, hypoplasia, mandibulofacial dysostosis (Treacher‐Collins syndrome), or congenital malformations of the temporomandibular component . Most reported cases of unilateral SMG agenesis were asymptomatic, possibly because secretions from other salivary glands compensated for the aplasia . The pathogenesis of the unilateral absence of a major salivary gland without other developmental anomalies is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…7 Isolated agenesis of parotid gland is more common than that of submandibular gland. 8 Isolated submandibular gland agenesis is very rare with only a few cases reported till date.…”
mentioning
confidence: 99%